Development of emotions and emotion regulation - Holodynski, Manfred 1957-; Friedlmeier, Wolfgang 1960- (Kluwer international series in outreach scholarship, 2005)
While there are many standard theories of the origin and purpose of emotions, Development of Emotions and Emotion Regulation departs from traditional viewpoints to offer new and provocative insights